CARBON RELIANCE ON DISSOLVED INORGANIC CARBON OF JUNIOR AND MATURED REED BEDS INDICATED BY STABLE ISOTOPE ANALYSIS - K. Zhao; M. Zhang; J. Xu (Journal of Animal and Plant Sciences, 2019)
Reed is one of the most widespread and productive wetland plant species worldwide, but few studies have addressed carbon utilization of this plant in natural environments. By collecting reed samples from lakes and ponds in the middle and lower reaches of the Yangtze River, weexamine the association between the carbon isotopic ratio (δ13C) of reed stem and root, and dissolved inorganic carbon concentration (DIC) and δ13CDIC, respectively. Our results suggest that 1) although atmospheric carbon is the dominant pathway, the pathway that uptake DIC through root system also plays an important role in determining the carbon stable isotope signal of reed, and 2) juvenile reedbed incorporates more carbon resources from DIC pool than the matured ones. Our study demonstrated that δ13C of emergent macrophytes could also be influenced by underwater carbon, especially at their early life stages.
Keywords: Carbon utilization; littoral habitat; reed; stable carbon isotope; wetland